Konstruksi Pendidikan Pembebasan dalam Al-Madrasatul Diniyah Lil Banat (Diniyah Putri) oleh Syekhah Hajjah Rangkayo Rahmah El-Yunusiyyah - Munawir Munawir; Alfita Choirun Amalia (JECED : Journal of Early Childhood Education and Development, 2023)
This research is a type of qualitative research. The approach to this study uses a character study approach by considering the character's integrity, depth of knowledge, and the success of the field the character is in. While the data collection method uses the documentation method, while the analysis uses content analysis while the technical data analysis uses hermeneutic techniques, which depart from language analysis and then move on to context analysis.Â The results of the study show (1) Awareness in the context of education for the liberation of Rahmah el-Yunusiyah which is divided into two aspects, internal and external. In the internal aspect, equipping students with various religious knowledge, languages, and various skills to develop the potential of each student can be empowered according to the field of interest. Awareness in the external aspect is proven by Rahmah with the real role of the daughter's daughter in the independence of the Indonesian nation (2) Rahmah El-Yunusiyyah uses the classical education method with a measurable grade system. He also applies a dormitory model so that his students can focus and be comfortable studying and avoid the prying eyes of married men